A dictionary of African mythology the mythmaker as storyteller - Scheub, Harold (Oxford Univ. Press, 2000)
"In this collection of hundreds of tales, Harold Scheub captures the sweep and diversity of African mythology. Scheub offers a collection of 400 stories, arranged alphabetically, that touch on virtually every aspect of religious belief. Here are gods and goddesses, epic heroes and divine tricksters, along with epics of the world's origins, the struggle between the human and the divine, and much more. Scheub covers the entire continent, from the mouth of the Nile to the shores of the Cape of Good Hope, including North African as well as sub-Saharan cultures. Scheub not only retells each story, but provides information about the respective belief system, the main characters, and related stories or variants. He also includes African proverbs, commentary on mythic themes and three appendices organized by country, linguistics/culture, and The Grand Myth. Perhaps most important, Scheub emphasizes the role of mythmaker as storyteller - as performer for an audience."--BOOK JACKET.